1998
DOI: 10.1111/j.1439-0329.1998.tb01182.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative susceptibility of Salix clones to chrysomelid beetles: evidence from the Stott willow collection at Ness

Abstract: Willow species and hybrids growing in the Stott willow collection at Ness, UK, differed markedly in their susceptibility to leaf damage by inseets, predominantly ehrysomelid beetles, with the rank order of suseeptibility remaining relatively constant over 2 years. Some species displayed a wide range of variation in susceptibility amongst clones; others very little. The range of susceptibilities of hybrids tended to mirror those of the parent species, with the hybrid usually sustaining leaf damage levels interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
(37 reference statements)
1
4
0
Order By: Relevance
“…3a, b). Differences in beetle feeding amongst the clones, however, support the earlier findings that willow susceptibility to leaf beetles is strongly controlled by genetics (Hodkinson et al 1998;Glynn et al 2004). There was no clear relationship between growth and insect feeding at both sites.…”
Section: Discussionsupporting
confidence: 78%
“…3a, b). Differences in beetle feeding amongst the clones, however, support the earlier findings that willow susceptibility to leaf beetles is strongly controlled by genetics (Hodkinson et al 1998;Glynn et al 2004). There was no clear relationship between growth and insect feeding at both sites.…”
Section: Discussionsupporting
confidence: 78%
“…There are some 30-40 species of Melampsora on Salix, each occurring on a specific range of willows. Except for M. amygdalinae, all willow rusts having five-spore stages require taxonomically very different plants (alternate hosts) to complete their lifecycle [18]; (4) Several authors have reported that S. triandra differs from most other willow species in its low content of glycosides and extremely low content of tannins (in laboratory-grown plants), although both secondary compounds are common in Salix [35]; (5) S. triandra also contains the highest concentration of salidroside, which is apparently a very rare glycoside in European willow species [59], and it has been argued that the rather high resistance of S. triandra to insects [25,61] may be attributed to this trait [24,28,41,56,61].…”
Section: Salix Triandra and Subgenus Salixmentioning
confidence: 99%
“…In the former case, it can lead to premature leaf‐abscission and in the latter to total defoliation of S. triandra ramets. Rust infection as well as leaf beetle damage and attacks by galling sawflies have been documented to affect growth and survival of willows (Bach 1994, Hodkinson et al 1998, Kendall and Wiltshire 1998, Hakkarainen et al 2005). We have not estimated the effect of our natural enemies on clone fitness and we are therefore unable to determine the strength of selection on specific plant traits.…”
Section: Discussionmentioning
confidence: 99%